(untitled) (Fiep Bulletin - online, 2012)
The course on Adapted Physical Education taught at Italian Universities is aimed at offering studentscompetences to improve the quality of life of the people involved in the practice of motor activities.Personalizing educational intervention means to apply the paradigms of adapted physical education to schoolsconsidering the concepts of Ability and Performance. These competences, if not adapted or personalized to everyone’sneeds, potentials and rhythms, represent a risk of limitations and restrictions, creating an additional gap in disabledstudents. The personalization of didactic processes also implies organizational and didactic choices regardingspaces/places, tools/gears, length and quantity of a motor assignment, its intensity and difficulty, breaks, time ofengagement, variety, groups, rules, ways of control and evaluation.Adapted Physical Activity is a didactic action aimed at allowing people to express their individual motor skills,regardless of their age or their physical state of health. It involves the social, emotional, motor, and cognitivedimensions of the personality.